Implementation of Tolerance Values for Vocational School Catholic Students in Samarinda City - Anjelin Agnes Nosar, Ludovika; Samdirgawijaya, Wilfridus (PT Literasi Nusantara Publisher, 2022)
This study examines the implementation of tolerance values ​​for students at Catholic 2 WR. Soepratman Samarinda, by focusing on student learning activities and the teacher's role. As a scientific study, this study uses a qualitative approach. Interview, observation, and documentation methods were used to collect data from three informants: the vice principal for curriculum, the Catholic religion teacher, and students. The data collected was then analyzed descriptively. The results of this study indicate that the values ​​of tolerance in Catholic schools are applied in learning activities that emphasize the school's vision and mission, namely excellence, love, and care, and are supported by the teacher's role as a role model for students. The model of tolerance patterned in this school is as follows: First, the learning process at school emphasizes a combination of excellence, love, and care. Second, multicultural school members of various religions (Catholic, Protestant, Hindu, and Buddhist) in one education system, namely Catholic education; Third, collective prayer is an activity that must be attended by all school members regardless of religious differences. Fourth, spiritual lessons are a way to educate and invite students to do good and warn students not to do evil. Fifth, the teacher becomes a positive role model for students in the school community and teaches from the perspective of the Catholic faith. The implementation of the values ​​of tolerance in the school environment plays a vital role in realizing religious freedom in a pluralistic religious society, especially in Indonesia.